2008
DOI: 10.21000/jasmr08010878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Substrate Composition on Microbial Community Structure of Pilot-Scale Biochemical Reactors Treating Mining Influenced Water

Abstract: Mining-influenced water (MIW) is acidic, metal rich water formed when sulfide minerals react with oxygen and water. There are various options for the treatment of MIW; however, passive biological systems such as biochemical reactors (BCRs) have shown promise because of their low cost and maintenance requirements. The purpose of this study was to explore the effect of organic substrate on microbial communities present in pilot-scale BCRs treating MIW in order to understand how substrate-microbe interactions dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Compared to the other inoculated columns, the EtOH columns contained the fewest mcrA genes (methanogens). This result supports a previous report by Prieto et al (2008), in which methanogens were lowest in concentration in ethanol-fed as compared to lignocellulose-fed BCRs. Suppressed methanogens may be advantageous considering that they compete with SRB for resources.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the other inoculated columns, the EtOH columns contained the fewest mcrA genes (methanogens). This result supports a previous report by Prieto et al (2008), in which methanogens were lowest in concentration in ethanol-fed as compared to lignocellulose-fed BCRs. Suppressed methanogens may be advantageous considering that they compete with SRB for resources.…”
Section: Discussionsupporting
confidence: 93%
“…For further primer validation, samples collected from two pilot-scale sulfate-reducing biochemical reactors that receive mine drainage from the National Tunnel in Black Hawk, CO (39) 58.8掳C, and 60.1掳C (mcrA). The optimized annealing temperature was selected based on the presence of one PCR product band of the expected size on a 1.2% agarose gel for the positive controls and the absence of any product in the pure-culture negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…These elevated metal concentrations and low pH contribute directly to conditions toxic for aquatic life and exceed the EPA ambient aquatic standards (Table 1, 6.0-6.6 4.8-6.4 6.5-8.5 Temperature 6.2-17.1 4.6-9.2 N/G 2 1 Current National Ambient Water Quality Criteria (U.S. EPA, 2004) 2 Not a goal for this study The BCRs supported active sulfate reducing bacterial communities (Prieto et al 2008) and demonstrated the removal of metals including Fe, Cu, and Zn from National Tunnel MIW over the course of six months in 2006 (Buccambuso et al 2007). Biogenic sulfide and elevated alkalinity were presumed to be responsible for metal removal in the BCRs, primarily by raising MIW pH to circum-neutral values and subsequent precipitation of metals in carbonate and sulfide forms.…”
Section: Introductionmentioning
confidence: 99%